Pengaruh Ukuran Perusahaan, Struktur Modal, dan Pertumbuhan Perusahaan terhadap Nilai Perusahaan - Kurniawan Kurniawan; Nurainun Bangun; Henryanto Wijaya; Thea Rahardjo (Universitas Matana, 2019)
The value of the company becomes an important thing related to the acquisition of funds through investment. Investors make the value of the company as an important consideration for investing. Companies must try to increase the value of their company to attract investors. The purpose of the research is to empirically examine the effect of company size, capital structure, and growth on firm value. The population used in this study is the manufacturing industry listed on the Indonesia Stock Exchange for the period 2014-2016. By using purposive sampling technique. The statistical method used to test hypotheses is multiple linear regression models and tested using SPSS. The results of this study indicate that there is a significant effect of firm size on firm value, there is no significant effect of capital structure on firm value, and there is a significant effect of growth on firm value. Simultaneous testing shows that there are significant effects of variable firm size, profitability, and capital structure on firm value.